2000
DOI: 10.1016/s0378-1097(00)00314-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of the 35-kb pvd locus and analysis of novel pvdIJK genes implicated in pyoverdine biosynthesis in Pseudomonas aeruginosa

Abstract: Novel putative pyoverdine synthetase pvdIJK genes were found upstream of pvdD in the 6.2-Mb chromosome of Pseudomonas aeruginosa strain PAO1. These genes formed a locus implicated in pyoverdine biosynthesis. Sequence analysis showed that the product of these genes shared 43%, 60% and 57% identity with PvdD. PvdIJK are thought to be implicated in synthesis of pyoverdine, a siderophore chelating Fe 3 . A pvdI mutant was obtained by gene disruption mutagenesis and confirmed by Southern hybridization. The pvdI mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…output ratio of mutant when compared to wild-type strain, divided by the c.f.u. input ratio of mutant to wild-type strain (Lehoux et al, 2000). The final CI was calculated as the geometric mean for animals in the same group, and experiments were done at least in triplicate (Hava & Camilli, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…output ratio of mutant when compared to wild-type strain, divided by the c.f.u. input ratio of mutant to wild-type strain (Lehoux et al, 2000). The final CI was calculated as the geometric mean for animals in the same group, and experiments were done at least in triplicate (Hava & Camilli, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…These genes are thought to encode peptide synthetases (Lehoux et al, 2000;Merriman et al, 1995), a family of proteins with many conserved sequence features . PvdD directs incorporation of two L-threonine residues into pyoverdine PAO (Ackerley et al, 2003) and pvdI and pvdJ are very likely to encode peptide synthetases that direct incorporation of the remaining six amino acids into the peptide of type I pyoverdines.…”
Section: Detection Of Pvd Gene Homologues In Other Pseudomonas Strainsmentioning
confidence: 99%
“…The product of the pvdD gene is a peptide synthetase that directs incorporation of two L-threonine residues into the peptide of pyoverdine PAO Ackerley et al, 2003). The pvdIJK gene products also have the characteristics of peptide synthetases (Lehoux et al, 2000); resequencing of P. aeruginosa PAO1 DNA shows that pvdJ and pvdK are part of a single gene (see below), which will be referred to here as pvdJ. The product of the pvdE gene is likely to be an ABC transporter protein and it is essential for pyoverdine synthesis (McMorran et al, 1996) although the transported substrate has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…PVDs are composed of a conserved dihydroxyquinoline chromophore, a variable peptide chain, comprising 6-12 amino acids, specific to a producing strain, and a side-chain, generally a dicarboxylic acid or an amide (Ravel & Cornelis, 2003). Both the chromophore and the peptide chain of PVDs are synthesized by non-ribosomal peptide synthetases (Merriman et al, 1995;Lehoux et al, 2000;Mossialos et al, 2002). Ferribactin, the precursor of PVD, is probably exported to the periplasm where it is matured into PVD with a chromophore .…”
Section: Introductionmentioning
confidence: 99%